2020
DOI: 10.1002/elan.202060172
|View full text |Cite
|
Sign up to set email alerts
|

Glassy Carbon Electrode Modified with Layering of Carbon Black/Poly(Allylamine Hydrochloride) Composite for Multianalyte Determination

Abstract: An electrochemical sensor using glassy carbon electrode modified with carbon black within a poly(allylamine hydrochloride) film is proposed in this work. The novel sensor was characterized by scanning electron microscopy, electrochemical impedance spectroscopy, and cyclic voltammetry using the redox probe Fe(CN)63−/4−. The sensor was applied for the simultaneous determination of dopamine (DA), paracetamol (PAR), amlodipine (AML), and rosuvastatin (RSV). The quantification of all four analytes was carried out b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Detection limit [μM] GCE 2.5-50 (2.5-90) [31] 0.25(� 0.02) (0.15) [31] 1.614(� 0.211) (1.0) [31] GCE/CB 0.25-10 (1.0-22) [32] 7.77(� 1.13) (0.38*) [32] 0.196(� 0.030) (0.55) [32] GCE/GO 0.1-10 (1.0-40) [33] 74.87(� 4.19) (0.318*) [33] 0.084(� 0.011) (0.69) [33] GCE/CND 0.75-20 (0.15-150) [27] 0.403(� 0.04) (3.74*) [27] 0.503(� 0.123) (0.026) [27] * μA/μM ChemElectroChem nounced with increasing concentration of 5-HT. Again, electrodes coated with carbon black produce a shifting baseline.…”
Section: Serotoninmentioning
confidence: 99%
“…Detection limit [μM] GCE 2.5-50 (2.5-90) [31] 0.25(� 0.02) (0.15) [31] 1.614(� 0.211) (1.0) [31] GCE/CB 0.25-10 (1.0-22) [32] 7.77(� 1.13) (0.38*) [32] 0.196(� 0.030) (0.55) [32] GCE/GO 0.1-10 (1.0-40) [33] 74.87(� 4.19) (0.318*) [33] 0.084(� 0.011) (0.69) [33] GCE/CND 0.75-20 (0.15-150) [27] 0.403(� 0.04) (3.74*) [27] 0.503(� 0.123) (0.026) [27] * μA/μM ChemElectroChem nounced with increasing concentration of 5-HT. Again, electrodes coated with carbon black produce a shifting baseline.…”
Section: Serotoninmentioning
confidence: 99%
“…Initially, CB was dispersed in DMF, which is a better approach to disperse CB in DMF than water [34]. A dispersion of 2 mg CB in 1 mL of DMF was prepared in an ultra-sonic bath for 1 h at room temperature.…”
Section: Preparation Of the Cb-bot/gcementioning
confidence: 99%
“…Recently, the development of biosensors based on polyelectrolytes-nanomaterials composites gained much attention from scientific community; for example, Zhao et al have demonstrated enzymatic electrochemical biosensor based on poly-L-lysine/black phosphorus hybrid [38]. Scremin et al have developed poly(allylamine hydrochloride)/carbon black composite based electrochemical sensor to detect multi-analytes [39]. Polyelectrolyte films have the advantage of lessen the effect of the interferences having opposite charge to analyte that could reach the electrode surface.…”
Section: Introductionmentioning
confidence: 99%